Parry, Kyle. A Theory of Assembly: From Museums to Memes. Routledge, 2023. 331 pp. ISBN 978-1-5179-1315-1 - Papp, Dávid (FOCUS: Papers in English Literary and Cultural Studies, 2024)
As it is often discussed in cultural theory and philosophy, the link between the “whole” and its constituents is more convoluted and abstract than it seems. Sometimes it cannot even be determined what the smallest unit of a system or structure is, or how the interplay between the elements of the whole affects what we call its meaning. The issue becomes infinitely more complicated as one moves from, for example, the meaning of individual utterances to that of complex structures made of a great many signifiers—such as images—where the question “what does it mean” seems to require a leap of faith across an infinite chasm. Gilles Deleuze and Felix Guattari were thinkers who leapt over many similar conceptual fissures; they often connected unexpected constituents to change the way the whole is viewed. “Assemblage,” “rhizome,” and “deterritorialization” are among their key words used to denote surprising connections between seemingly incompatible elements. As such, they enjoy widespread usage among researchers who wish not just to show what something is made of, but also how revisiting the connection between its elements can change how the whole is perceived. In A Theory of Assembly: From Museums to Memes, Kyle Parry sets out to argue in a broadly Deleuzian fashion that there is an organizing force between “plywood and keywords to epoxy, pixels, and people” which makes up art, exhibitions, memes, and even whole communities (47).